FACTORS INFLUENCING FOREST ENCROACHMENT IN PTVI AREA AND ITS ECONOMIC IMPACT - Maulana Mahendra; Kurniawati Kurniawati (JURNAL ILMIAH EDUNOMIKA, 2024)
Background - Forest encroachment refers to the process of reducing forest area due to human activities, such as logging, agricultural land clearing, mining, and infrastructure development. This phenomenon is of global concern as it has serious impacts on the environment, biodiversity and climate. Objective - The purpose of this study was to determine the impact of forest encroachment and determine the factors that cause forest encroachment in the Sorowako Block Area, East Luwu Regency, South Sulawesi where PTVI is located. Design/methodology/approach - The research method used in this article is qualitative method and descriptive analysis technique. Findings - The results of this study concluded that the factors influencing forest encroachment are the lack of certainty of the tenure system, the high economic value of land use by non-companies, the weak supervision system of the contract of work, not optimal law enforcement efforts and the weak dispute resolution mechanism in the PTVI system. Economic factors in the surrounding environment are the main factors influencing forest encroachment. Research implication - It is important for companies to integrate environmental considerations in business decision-making in order to achieve long-term sustainability and avoid the negative economic impacts of forest encroachment. Limitations of Research - Analyses may be limited to a particular region or country, so the results may not be directly applicable elsewhere.